Cyber-physical and gentelligent systems in manufacturing and life cycle : genetics and intelligence -- keys to industry 4.0 /: genetics and intelligence -- keys to industry 4.0. ([2017]) - Denkena, Berend; Mörke, Tobias
No abstract available